Penerapan bagi hasil pembiayaan musyarakah pada bank pembiayaan syariah - Nurma Sari; Alma Herdian (FEBI IAIN Langsa, 2021)
This study aims to determine how the application of revenue sharing for musyarakah financing at BPRS XXX and whether the application of revenue sharing revenue for musyarakah in BPRS is in accordance with DSN Fatwa No. 08/DSN-MUI/IV/2000. This study uses a qualitative descriptive approach with the Grounded Research method. Data collection was carried out by interviewing several related parties in the BPRS, namely the Head of Marketing, Legal Officer, Sharia Supervisory Board, and musyarakah financing customers. The results of his research on the application of revenue sharing for musyarakah financing at BPRS have been carried out in accordance with DSN Fatwa No. 08/DSN-MUI/IV/2000. All provisions regarding musyarakah financing in the DSN Fatwa have been implemented by the BPRS, such as the ijab qabul, the subject of the contract, the object of the contract consisting of capital, work and profits, as well as operational and dispute costs. It's just that the distribution of losses applied by the BPRS is not in accordance with the fatwa, where the BPRS applies losses fully borne by the customer, not in accordance with the provisions of the Fatwa DSN which says that losses are jointly borne in accordance with their respective portion of capital.